‘Pulled’ or ‘Pushed’? The Emigration of Portuguese Scientists - Delicado, Ana (2019)
This chapter addresses the migration of scientific professionals from Portugal in the past few decades, focusing on the ‘pull’ (which attract skilled workers to a country) and “push” (which repel workers away from the country of origin) factors that drive this migration. Based on official statistics, a questionnaire survey with researchers abroad and semi-structured interviews with returnee scientists, the chapter shows how Portugal, as a semi-peripheral country, has traditionally been a sending rather than a receiving country for scientists. Exit trends were actively encouraged throughout the last few decades by national science policies (training of human resources that provided opportunities for studying and working abroad) and by European policies (of intra-EU mobility). Similarly, the growth of resources in the Portuguese scientific system came to be a factor for attracting foreign scientists to Portugal. Mobility rates, both outbound and return, were high but over time push factors became less significant, as Portugal increased its attractiveness for young researchers wishing to pursue advanced training and even for foreign researchers. However, in later years, the economic crisis and the austerity measures implemented to deal with it, as well as some changes in science policy, have created favourable conditions for an increase in brain drain.